EP797 20 years of ultra radical surgery for ovarian cancer patients in perth western australia, what have we learnt?. (1st November 2019) - Baxter, L; Ayres, C; Cohen, P; Kader Ali Mohan, R; Leung, Y
Abstract : Introduction/Background: Primary cytoreductive surgery followed by adjuvant taxane- and platinum-based combination chemotherapy are the standard treatments for advanced ovarian cancer in most patient populations. Much has been debated regarding the competing perspectives of the tumour biology versus the value of aggressive surgical resection in ovarian cancer as major survival determinants. Many recent studies have showed significant survival advantages for optimally cytoreduced patients. Secondary to this many gynaecological unites, including out own, has adopted a policy of aggressive cytoreduction, often involving bowel resection. The detraction however from ultra-radical surgery is the associated morbidity of ultra-radical surgery. The aim of this study is to assess radical debulking of ovarian cancer with concomitant rectosigmoid resection, with respect to perioperative complication rates and its impact on survival following surgery in a tertiary unit in Perth Western Australia. Methodology: A retrospective review was performed of the case notes of 164 consecutive procedures performed between 2000 and 2017 in a regional cancer centre. Results: 11.4% of patients suffered some form of complication during admission. Anastomotic complications were rare, occurring in only 1.5% of patients. Perioperative mortality was 2.6%. Overall mean survival was 45 months. Mean survival and progression free survival were significantly longer in the ultra-radical group. Conclusion: Ultra-radical surgery for ovarian cancer ensure optimal cytoreduction and increased median survival time, with low rates of intra operative and post operative morbidity. Disclosure: Nothing to disclose.